BODY EDUCATION IN MACAPÁ/AP-BRAZIL (1944): WHAT DOES THE PHOTOGRAPH PICTURES TELL US? (Fiep Bulletin - online, 2011)
This trial intends to reflect, in an specific way, about the body education on a public school in the city of Macapá/AP-Brazil in 1944, through reading of gymnastic photograph pictures. To bring it into focus, it will be taken as reference the analysis of some pictures from the time mentioned starting from the concepts of time, space and body discipline in a political project of the Brazilian's "New State".
Keywords: Body Education; Brazil; Photograph Picture